EFFECT OF E-COMMERCE INNOVATION AND E-SERVICE QUALITY ON TOKOPEDIA CUSTOMER SATISFACTION AND LOYALTY IN SURABAYA - Wibowo, Felix Arvinto; Trisnawati, Juliani Dyah; Megawati, Veny (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
Recent developments have encouraged changes in people's shopping styles, from conventional to online. The online shopping style that society continues to adopt also influences the basis of people's decisions in determining which e-commerce to choose to fulfill people's online shopping activities. This research will analyze the influence of e-commerce innovation, e-service quality, customer satisfaction, and loyalty on Tokopedia customers in Surabaya. This research uses a quantitative approach with primary data in the form of a questionnaire, which is distributed and analyzed using the Structural Equation Modeling (SEM) method with the help of SmartPLS 4.0 software. The results of this research found that e-commerce innovation has a positive impact on customer satisfaction and customer loyalty. E-service quality has a positive impact on customer satisfaction but not a significant impact on customer loyalty. Customer satisfaction has a positive impact on customer loyalty. Customer satisfaction mediates the development of e-commerce innovation and e-service quality on customer loyalty. A thorough understanding of the factors that influence customer satisfaction is essential in gaining customer loyalty for e-commerce companies in Indonesia. Companies must be able to adapt the innovations and the quality of electronic services provided to the factors that influence customer satisfaction.